comparison of agricultural income in Hungary and the New Federal States of Germany - Baráth, Lajos (Acta Agraria Debreceniensis, 2008)
There are a lot of literatures that investigate the agricultural transition both in Hungary and former GDR. However there is no one, which examines and compares the income situation in the above mentioned countries. The aim of this article is to analyse that. The investigation is based on the data of Economic Accounts for Agriculture (EAA). The result shows that the agricultural income is much higher in the New Federal States of Germany if we take into account the subsidies, however without subsidies it would be higher in Hungary.